2015
DOI: 10.1007/s10668-015-9729-8
|View full text |Cite
|
Sign up to set email alerts
|

Urban sprawl, public transport, and increasing CO2 emissions: the case of Metro Manila, Philippines

Abstract: Current international discussions on the increasingly critical levels of carbon emissions from the transportation sector commonly attribute the causality chain to urban sprawl growth-private car use-carbon emission. An often assumed development context of this causality chain is that common of developed country urbanization. However, in the particular context of developing country urbanization, urban sprawl and associated workplace-home distanciation may lead to more intensive use by the urban workforce of pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Plaut [ 69 ], Choi and Ahn [ 70 ], and Carse et al [ 71 ] have also shown that car ownership is strongly associated with a reduced likelihood of choosing non-motorized modes of transportation, and the higher the number of cars available per adult in the household, the more likely that the trip would be made by non-low-carbon transport modes. Hence, reducing dependency on cars, including through the control of vehicle ownership and vehicle use intensity, improving public transport and non-motorized infrastructure and services, and developing new, cleaner fuel and fuel-efficient vehicles could be more effective strategies to reduce energy consumption, GHG emissions, and the adverse effects of environmental pollution in Chinese cities [ 7 , 72 , 73 ]. It was observed that males were 1.928 times more likely to use non-low-carbon modes for shopping than females.…”
Section: Resultsmentioning
confidence: 99%
“…Plaut [ 69 ], Choi and Ahn [ 70 ], and Carse et al [ 71 ] have also shown that car ownership is strongly associated with a reduced likelihood of choosing non-motorized modes of transportation, and the higher the number of cars available per adult in the household, the more likely that the trip would be made by non-low-carbon transport modes. Hence, reducing dependency on cars, including through the control of vehicle ownership and vehicle use intensity, improving public transport and non-motorized infrastructure and services, and developing new, cleaner fuel and fuel-efficient vehicles could be more effective strategies to reduce energy consumption, GHG emissions, and the adverse effects of environmental pollution in Chinese cities [ 7 , 72 , 73 ]. It was observed that males were 1.928 times more likely to use non-low-carbon modes for shopping than females.…”
Section: Resultsmentioning
confidence: 99%
“…If cities increase the market share of their public transit system by replacing cars or other high-carbon emission transport modes, they reduce their carbon footprint. However, if HSR or the public transit system in cities induce more travel demand through a substitution effect to high-carbon emission transport modes emissions, the net carbon footprint is ambiguous [57,58].…”
Section: Background and Conceptual Analytic Frameworkmentioning
confidence: 99%
“…There are significant relationships between the socio-economic variables and respondents' preference for public transport, hence socio-economic variables can be used to create infrastructural improvements and designs that are more attractive for promoting an increase in public transport users, especially with groups of females, students, the elderly and low income earners who prefer to use public transport before policy interventions. As stated in Chidambaram, et al [68] reducing the use of cars has not often been achieved voluntarily, complementary measures and actions are needed to promote the viability of the switch of car users to public transport, including car use restrictions, car and fuel taxes, road pricing, congestion charging, parking constraints and parking costs, and notable technology improvements and innovations of new clean energy and fuel efficient vehicles, which have been adopted in parts of cities to promote public transport and reduce the adverse effects of environment pollutants [66,[68][69][70].…”
Section: Policy Implicationsmentioning
confidence: 99%